2020
DOI: 10.3389/fmicb.2019.02870
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and Time Can Alter Epibacterial Communities of an Invasive Seaweed

Abstract: The establishment of epibacterial communities is fundamental to seaweed health and fitness, in modulating ecological interactions and may also facilitate adaptation to new environments. Abiotic factors like salinity can determine bacterial abundance, growth and community composition. However, influence of salinity as a driver of epibacterial community composition (until species level) has not been investigated for seaweeds and especially under long time scales. We also do not know how abiotic stressors may inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…However, natural changes in SST observed across this study were markedly lower than those used in previous short‐term climate change experiments: 4–14°C (Li et al, 2018; Lokmer & Wegner, 2015) versus a range of ~1.6°C from 2008 to 2011. Similarly, differences in salinity have been shown to alter microbiome composition in experiments with multiple hosts including seaweeds (Saha et al, 2020) and corals (Röthig et al, 2016), although salinity variations in such experiments (8–19 practical salinity units (psu)) are typically much larger than the natural variations seen here (<0.1 psu). Decade‐scale microbiome differentiation has been previously shown in the human gut, although nearly 60% of bacterial phylotypes persisted over more than a decade (Faith et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…However, natural changes in SST observed across this study were markedly lower than those used in previous short‐term climate change experiments: 4–14°C (Li et al, 2018; Lokmer & Wegner, 2015) versus a range of ~1.6°C from 2008 to 2011. Similarly, differences in salinity have been shown to alter microbiome composition in experiments with multiple hosts including seaweeds (Saha et al, 2020) and corals (Röthig et al, 2016), although salinity variations in such experiments (8–19 practical salinity units (psu)) are typically much larger than the natural variations seen here (<0.1 psu). Decade‐scale microbiome differentiation has been previously shown in the human gut, although nearly 60% of bacterial phylotypes persisted over more than a decade (Faith et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…Bacterial biodiversity often varies among different macroalgal hosts in a single location (Lachnit et al, 2009;Weigel and Pfister, 2019), within the same macroalgal host in different biogeographic regions (Roth-Schulze et al, 2018;Morelan et al, 2019), by tissue (Staufenberger et al, 2008;Quigley et al, 2018;Weigel and Pfister, 2019;Paix et al, 2020), or due to abiotic changes (Tujula et al, 2010;Michelou et al, 2013;Miranda et al, 2013;Longford et al, 2019;Qiu et al, 2019;Saha et al, 2020). Extensive studies of the biodiversity of bacteria on Baltic Sea Fucus vesiculosus, which is not usually exposed to air (Medvedev et al, 2016), found effects of different salinities (Stratil et al, 2014) and higher temperature (Stratil et al, 2013;Mensch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, that examined, through the use of metagenomic sequencing, the influence of various salinities (low, medium, and high) at different times (i.e., 3 and 5 months) on a sampling of epibacterial community of an invasive red seaweed Agarophyton vermiculophyllum (Ohmi) Gurgel, J.N. Norris et Fredericq, formerly Gracilaria vermiculophylla (Ohmi), revealed that the epibacterial richness varied both irrespectively of the salinity levels and time points [ 160 ]. Thus, it has been concluded by the authors that both salinity and time can be major driving forces in structuring epibacterial communities of seaweeds with respect to richness and diversity.…”
Section: Spatial-temporal Exploration and Functional Distribution mentioning
confidence: 99%